THE IMPORTANCE OF TIME TO INTERVENTION IN RUPTURED ABDOMINAL AORTIC ANEURYSM TIME TO INTERVENTION IN rAAA - NARRATIVE REVIEW - Szlegiel, Igor; Gwiaździńska, Oktawia; Strzykała, Anita; Lewandowski, Jakub; Hovsepyan, Izabela; Myszak, Denis (International Journal of Innovative Technologies in Social Science, 2026)
Ruptured abdominal aortic aneurysm (rAAA) remains one of the most formidable emergencies in vascular surgery and continues to be associated with substantial mortality and morbidity de-spite major advances in diagnostic imaging, perioperative management, anesthesia, and endo-vascular therapy. The clinical challenge lies not only in the catastrophic nature of the rupture itself, but also in the narrow temporal window available for diagnosis, transfer, and definitive hemorrhage control. Contemporary pathway-based care models therefore emphasize that treatment should follow diagnosis with the least possible delay, and many systems operationalize this urgency through a target intervention interval of 90 minutes or less. Over the past three decades, the management of rAAA has evolved substantially through im-proved imaging availability, greater use of coordinated transfer networks, more selective pre-hospital and early in-hospital resuscitation strategies, better patient selection for open and endo-vascular repair, implementation of standardized emergency pathways, and increased awareness of major postoperative complications such as renal failure, abdominal compartment syndrome, and multiorgan dysfunction. These developments, together with advances in perioperative physiological optimization and critical care support, have contributed to gradual improvement in reported outcomes in modern series. Nevertheless, postoperative morbidity and mortality re-main high, and contemporary reports still describe substantial death rates among treated patients. Only a minority of patients appear to undergo definitive repair within the recommended time window, underscoring the persistent gap between guideline-driven expectations and real-world emergency system performance. Although current evidence suggests that the ≤90-minute benchmark may have limited independent association with postoperative morbidity and mortality after adjustment for baseline risk and hemodynamic status, avoiding unnecessary delay re-mains a central principle of rAAA care. Time to intervention should therefore be understood not merely as a numerical target, but as a marker of system efficiency, diagnostic speed, transfer coordination, and readiness to deliver definitive treatment in a critically unstable patient.